2021
DOI: 10.1063/5.0057861
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved cathodoluminescence in an ultrafast transmission electron microscope

Abstract: Ultrafast transmission electron microscopy (UTEM) combines sub-picosecond time-resolution with the versatility of TEM spectroscopies. It allows to study the ultrafast materials response using complementary techniques. However, until now, time-resolved cathodoluminescence was unavailable in a UTEM. In this paper we report time-resolved cathodoluminescence measurements in an ultrafast transmission electron microscope. We mapped the spatial variations of the emission dynamics from nano-diamonds with a high densit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Besides their unmatched spatial resolution, free electrons can also serve as quantum-coherent probes. Ultrafast electron microscopy experiments demonstrated coherent interactions of free electrons and light (29)(30)(31)(32)(33)(34) and were also used to probe its quantum photonic nature (35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%
“…Besides their unmatched spatial resolution, free electrons can also serve as quantum-coherent probes. Ultrafast electron microscopy experiments demonstrated coherent interactions of free electrons and light (29)(30)(31)(32)(33)(34) and were also used to probe its quantum photonic nature (35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%
“…The use of a higher repetition-rate laser, for example, from 300 kHz in this study to several MHz, would increase the sampling rate by an order of magnitude. Using a field-emission gun as a brighter electron source in scanning TEM (STEM) that is conventional with a high current density, tr-CL can be mapped with a spatial resolution reaching approximately 10 nm. , The recent study, published while this work was under review, reported the implementation of tr-CL in STEM with a time resolution of sub-nanoseconds, demonstrating a higher sampling rate (2 MHz) and smaller probe size (12 nm) with the scanning capability …”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
“…24,75 The recent study, published while this work was under review, reported the implementation of tr-CL in STEM with a time resolution of sub-nanoseconds, demonstrating a higher sampling rate (2 MHz) and smaller probe size (12 nm) with the scanning capability. 76 With all the technical upgrades currently available, tr-CL spectroscopy coupled with UEM would allow for tracking energy-conversion processes in single-photon sources and single quantum dots. For an in-depth investigation on ultrafast materials dynamics at the nanoscale, combined access to transient electronic states of matter by both electrons and photons is highly desirable, which can be realized in UEM of correlative imaging and spectroscopy capability.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
“…7 Furthermore, time-resolved CL has emerged as a crucial tool for probing ultrafast dynamics of excited states in nanoscale materials. 8,9 Time-resolved CL can rely on pulsed electron beams generated with electrostatic beam-blankers 10 or pulsed-laser excitation of the electron gun, 11 but both of these approaches reduce the spatial resolution of the microscope and add to the complexity of the microscope column design. Ultrafast beam blankers in scanning electron microscopes (SEMs) limit the temporal resolution to ∼100 picoseconds and provide spatial resolution of ∼50 nm.…”
Section: Introductionmentioning
confidence: 99%